2011
DOI: 10.1111/j.1365-313x.2011.04501.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis genes IRREGULAR XYLEM (IRX15) and IRX15L encode DUF579‐containing proteins that are essential for normal xylan deposition in the secondary cell wall

Abstract: SUMMARYThere are 10 genes in the Arabidopsis genome that contain a domain described in the Pfam database as domain of unknown function 579 (DUF579). Although DUF579 is widely distributed in eukaryotic species, there is no direct experimental evidence to assign a function to it. Five of the 10 Arabidopsis DUF579 family members are co-expressed with marker genes for secondary cell wall formation. Plants in which two closely related members of the DUF579 family have been disrupted by T-DNA insertions contain less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 42 publications
(94 reference statements)
7
108
0
1
Order By: Relevance
“…Consistent with high pectin synthesis in the callus cells, we identified GAUT1, GAUT7, and many other GAUT family members in GT8 (Sterling et al, 2006;Atmodjo et al, 2011) as well as ARAD1 and XGD1 in GT47, involved in arabinan and xylogalacturonan synthesis, respectively (Harholt et al, 2006;Jensen et al, 2008). We also detected enzymes likely involved in primary cell wall glucuronoarabinoxylan synthesis: IRX10-L, IRX14, and two IRX15/DUF579 homologs (Brown et al, 2009(Brown et al, , 2011Wu et al, 2010;Jensen et al, 2011), and GUX3, a homolog of the GUX1 and GUX2 xylan glucuronosyltransferases (Mortimer et al, 2010). Proteins of extensin glycosylation (RRA3 and XEG113; Velasquez et al, 2011) and possibly glucomannan synthesis (CslD2 and CslD3; Yin et al, 2011) were identified as well, indicating that LOPIT also detects proteins synthesizing relatively minor cell wall components.…”
Section: Identification Of the Cell Wall Synthesis Machinery In The Gsupporting
confidence: 67%
“…Consistent with high pectin synthesis in the callus cells, we identified GAUT1, GAUT7, and many other GAUT family members in GT8 (Sterling et al, 2006;Atmodjo et al, 2011) as well as ARAD1 and XGD1 in GT47, involved in arabinan and xylogalacturonan synthesis, respectively (Harholt et al, 2006;Jensen et al, 2008). We also detected enzymes likely involved in primary cell wall glucuronoarabinoxylan synthesis: IRX10-L, IRX14, and two IRX15/DUF579 homologs (Brown et al, 2009(Brown et al, , 2011Wu et al, 2010;Jensen et al, 2011), and GUX3, a homolog of the GUX1 and GUX2 xylan glucuronosyltransferases (Mortimer et al, 2010). Proteins of extensin glycosylation (RRA3 and XEG113; Velasquez et al, 2011) and possibly glucomannan synthesis (CslD2 and CslD3; Yin et al, 2011) were identified as well, indicating that LOPIT also detects proteins synthesizing relatively minor cell wall components.…”
Section: Identification Of the Cell Wall Synthesis Machinery In The Gsupporting
confidence: 67%
“…Pectin and xylan synthesis occurs in the Golgi (Mohnen, 2008;Brown et al, 2011), and AGP synthesis initiates in the endoplasmic reticulum and continues in the Golgi (Oka et al, 2010;Wu et al, 2010). Thus, one possible mechanism for APAP1 biosynthesis is the addition of glycans onto AGP57C by either the consecutive addition of one residue at a time or by block addition, possibly occurring within the Golgi apparatus (Atmodjo et al, 2011(Atmodjo et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…6A), is derived from the GO term "chitin metabolic process" and also includes some PPIs, TF targets, and AraNet edges. The module contains five true-positive genes, MYB DOMAIN PROTEIN63 (MYB63; Zhou et al, 2009), IRREGULAR XYLEM15 (IRX15) and IRX15-L (Brown et al, 2011), NAC DOMAIN CONTAINING PROTEIN73 (ANAC073) (Zhong et al, 2008), and REDUCED WALL ACETYLATION1 (RWA1) (Lee et al, 2011), all of which were correctly predicted to be involved in cell wall biogenesis. MYB63 and ANAC073 are a MYB and a NAC TF, respectively, and whereas MYB63 was known to be involved in JA/SA response pathways (Yanhui et al, e Genes that were present in both conserved and nonconserved modules could gain a prediction by both.…”
Section: Module-based Functional Annotation Of Unknown Plant Genesmentioning
confidence: 99%